2023
DOI: 10.1055/a-2103-8329
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Osmotic Dilators for Pre-Induction Cervical Ripening – an Evidence-Based Review

Abstract: Mechanical methods have gained growing interest for pre-induction cervical ripening in women with an unripe cervix, since they have a better safety profile compared to prostaglandins. Balloon catheters have been the gold standard method for decades, while there was a lack of data on synthetic osmotic cervical dilators.Not until 2015, when Dilapan-S was approved by the Food and Drug Administration (FDA) for induction of labor, numerous studies have been published on the use of Dilapan-S in this fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Very few cases of osmotic cervical dilators have been reported and relates to the previous version of DIlapan 5 . In two of such cases reported in the literature, both were related to cervical ripening for termination of pregnancy 7,8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few cases of osmotic cervical dilators have been reported and relates to the previous version of DIlapan 5 . In two of such cases reported in the literature, both were related to cervical ripening for termination of pregnancy 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…It is an effective means of induction of labour with a very good safety profile and no known associated foetal complications due to its unlikely chance of causing uterine hyperstimulation 2,4,5 . Many large studies have found no cases of uterine tachysystole related to Dilapan-S use during cervical ripening and it is increasingly been used as an agent for outpatient induction of labour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation